UNESCO (2015). Education for all 2000-2015: Achievements and Challenges. EFA Global Monitoring Report 2015. Paris, France. Publication by the United Nations Educational Scientific and Cultural Organization. 499 pp. ISBN- 978-92-3-10085-0 - Preckler Galguera, Miriam (Journal of Supranational Policies of Education (JOSPOE), 2016)
Journal of Supranational Policies of Education (JoSPoE)